2009
DOI: 10.1208/s12249-009-9200-y
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Swellable and Floating Gastroretentive Ciprofloxacin Hydrochloride Tablets

Abstract: Abstract. Drugs that have narrow absorption window in the gastrointestinal tract (GIT) will have poor absorption. For these drugs, gastroretentive drug delivery systems offer the advantage in prolonging the gastric emptying time. Swellable, floating, and sustained release tablets are developed by using a combination of hydrophilic polymer (hydroxypropyl methylcellulose), swelling agents (crospovidone, sodium starch glycolate, and croscarmelose sodium) and effervescent substance (sodium bicarbonate). Formulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 21 publications
1
39
0
Order By: Relevance
“…The resultant blend was free flowing and further compressed using 12 mm round standard concave punch sets at 500 mg target weight. In the present formulation, sodium bicarbonate was used to generate carbon dioxide to increase buoyancy and crospovidone as swelling agent [27] as well as to increase hydration capacity [28] of tablets. The levels of sodium bicarbonate and crospovidone were fixed at 7% w/w and 10% w/w respectively.…”
Section: Qtpp Of Dpm Gastroretentive Floating Tabletsmentioning
confidence: 99%
“…The resultant blend was free flowing and further compressed using 12 mm round standard concave punch sets at 500 mg target weight. In the present formulation, sodium bicarbonate was used to generate carbon dioxide to increase buoyancy and crospovidone as swelling agent [27] as well as to increase hydration capacity [28] of tablets. The levels of sodium bicarbonate and crospovidone were fixed at 7% w/w and 10% w/w respectively.…”
Section: Qtpp Of Dpm Gastroretentive Floating Tabletsmentioning
confidence: 99%
“…The samples were filtered through a 0.45-μm membrane filter and diluted to a suitable concentration. The absorbance of these solutions was measured at 276 nm using a UV-vis spectrophotometer (Shimadzu 1800) (11). The percentage drug release was plotted against time to construct drug release profile for the formulation ( Figure 5).…”
Section: Marketed Floating Tablet Formulation Containing Ciprofloxacimentioning
confidence: 99%
“…It was observed that all tablet formulations floated longer than 12 h, excluding formulations C-X25 and C-X40 which disintegrated in 2 and 6 hours, respectively. These might be due to the high amount of crospovidone in the formulations and rapid hydration of xanthan gum (15). C-X50 3-4 3.10 ± 0.34 9 ± 0.9 > 12…”
Section: Characterization Of Floating Tabletsmentioning
confidence: 99%